164k views
22 votes
Solve the expression 6 x one sixth + 11 x 2

User Wtfzdotnet
by
5.4k points

2 Answers

6 votes
6 x 1/6 + 11 x 2

Since multiplication comes before addition in PEMDAS, you’ll need to do multiplication first. The first multiplication in this expression is 6 x 1/6 which can also be written as 6/1 x 1/6

6/1 x 1/6 = 1

The second multiplication in this equation is 11 x 2

11 x 2 = 22

Now you can add both of the numbers and you’d get 23 :)

1 + 22 = 23
User Druska
by
6.0k points
4 votes

Explanation:

6 x 1/6= 1

11 x 2= 22

22+1= 23

User Sourabh Sharma
by
6.1k points